Investigation of sanguinarine and chelerythrine effects on LPS-induced inflammatory gene expression in THP-1 cell line - Pěnčíková, K; Kollár, P; Müller Závalová, V; Táborská, E; Urbanová, J; Hošek, J (Phytomedicine, 2012)
Quaternary benzo[c]phenanthridine alkaloids sanguinarine and chelerythrine have been used in folk medicine for their wide range of useful properties. One of their major effect is also anti-inflammatory activity, that is not clarified in detail. This study focused on the ability of these alkaloids to modulate the gene expression of pro-inflammatory tumour necrosis factor α (TNF-α), monocyte chemoattractant protein 1 (MCP-1, also known as CCL-2), interleukin (IL)-6, IL-1β and anti-inflammatory cytokines IL-1 receptor antagonist (IL-1RA) and IL-10. The effect of these alkaloids was compared with that of conventional drug prednisone. Human monocyte-derived macrophages were pre-treated with alkaloids or prednisone and inflammatory reaction was induced by lipopolysaccharide. Changes of gene expression at the transcriptional level of mentioned cytokines were measured. In our study mainly affected pro-inflammatory cytokines were CCL-2 and IL-6. Two hours after LPS stimulation, cells influenced by sanguinarine and chelerythrine significantly declined the CCL-2 expression by a factors of 3.5 (p<0.001) and 1.9 (p<0.01); for those treated with prednisone the factor was 5.3 (p<0.001). Eight hours after LPS induction, both alkaloids significantly diminished the CCL-2 expression. The lower expression was found for sanguinarine--lower by a factor of 4.3 than for cells treated with the vehicle (p<0.001). Two hours after LPS stimulation, cells treated with sanguinarine decreased the IL-6 mRNA level by a factor of 3.9 (p<0.001) compared with cells treated with the vehicle. Chelerythrine decreased the level of IL-6 mRNA by a factor of 1.6 (p<0.001). Sanguinarine decreased gene expression of CCL-2 and IL-6 more than chelerythrine and its effect was quite similar to prednisone. Four hours after LPS stimulation, cells pre-treated with sanguinarine exhibited significantly higher expression (a factor of 1.7, p<0.001) of IL-1RA than cells without sanguinarine treatment. Our results help to clarify possible mechanisms of action of these alkaloids in the course of inflammation.
Keywords: genetická transkripce; Isoquinolines; Plant Extracts; exprese genu; Humans; antiflogistika; Gene Expression; Phytotherapy; fytoterapie; benzofenantridiny; lipopolysacharidy; Transcription, Genetic; Lipopolysaccharides; Interleukin-6; makrofágy; Prednisone; Benzophenanthridines; Inflammation; lidé; zánět; rostlinné extrakty; chemokin CCL2; buněčné linie; prednison; Cell Line; interleukin-6; Chemokine CCL2; Anti-Inflammatory Agents; Macrophages; Inflammation Mediators; mediátory zánětu; isochinoliny